Disturbance‐observer‐based output feedback control of non‐linear cascaded systems with external disturbance. Issue 6 (1st April 2018) - Wu, Kang; Zhang, Zhongcai; Sun, Changyin
Abstract : The output feedback robust controller is proposed for a class of non‐linear systems with integral input‐to‐state stable inverse dynamics and external disturbance. The investigated systems represent more general classes of non‐linear uncertain systems. An extended state observer (ESO) is designed to estimate both the system states and the external disturbance by use of the disturbance as a generalised state. Based on the given reduced‐order ESO, a new error dynamic system is constructed. The global asymptotic regulation is guaranteed under the presented anti‐disturbance controller by the combined approach of backstepping and linear matrix inequality. The simulation result demonstrates the effectiveness of the given algorithm.